Public Housing and Well-Being: Evaluation Frameworks to Influence Policy. (December 2020) - Rangiwhetu, Lara; Pierse, Nevil; Chisholm, Elinor; Howden-Chapman, Philippa
Background: A robust evidence base is needed to develop sustainable cross-party solutions for public housing to promote well-being. The provision of public housing is politically contentious in New Zealand, as in many liberal democracies. Depending on the government, policies oscillate between encouraging sales of public housing stock and reducing investment and maintenance, and large-scale investment, provision, and regeneration of public housing. Aim: We aimed to develop frameworks to evaluate the impact of public housing regeneration on tenant well-being at the apartment, complex, and community levels, and to inform future policies. Method: Based on a systems approach and theory of change models, we developed a mixed methods quasi-experimental before-and-after outcomes evaluation frameworks, with control groups, for three public housing sites. This evaluation design had flexibility to accommodate real-world complexities, inherent in evaluating large-scale public health interventions, while maintaining scientific rigor to realize the full effects of interventions. Results: Three evaluation frameworks for housing were developed. The evaluation at the apartment level confirmed proof of concept and viability of the framework and approach. This also showed that minor draught-stopping measures had a relatively big impact on indoor temperature and thermal comfort, which subsequently informed healthy housing standards. The complex and community-level evaluations are ongoing due to longer regeneration timeframes. Conclusion: Public housing is one of central government's larger social sector interventions, with Kāinga Ora – Homes and Communities the largest Crown entity. Evaluating public housing policies is important to develop an evidence base to inform best practice, rational, decision-making policy for the public as well as the private sector.